What dreams may come [videorecording (DVD)] - Ward, Vincent; Williams, Robin, 1951-2014; Gooding, Cuba, Jr., 1968-; Sciorra, Annabella; Sydow, Max von, 1929-2020-; Grant, Jessica Brooks; Chao, Rosalind; Kamen, Michael; Matheson, Richard, 1926-2013 (Polygram Video : Universal Studios [distributor, 2002)
Four years after Chris and Annie Nielsen lose their children in a traffic accident, Chris himself is killed and finds himself reunited with his children in a beautiful and astonishing afterlife, but Annie commits suicide in despair and is banished to a very different realm. Chris risks his own eternal happiness to find Annie and rescue her from her fate.